Design and experimental study of a sensitization structure with fiber grating sensor for nonintrusive pipeline pressure detection. (June 2020) - Yan, Zhidan; Chen, Guo; Xu, Chaoyu; Xu, Wenyi
Abstract: With the extensive applications of pressure pipelines in various fields, research on pipeline pressure nonintrusive detection technology has become a promising measurement technology and development trend. In this study, taking a pressure pipeline as the research object, a wall strain sensitization structure with a nonintrusive fiber Bragg grating (FBG) pressure sensor was proposed. First, the strain characteristics of the pipeline wall under internal pressure were analyzed in detail. Then, a nonintrusive strain-amplifying structure with a rhomboid structure as the core was designed in accordance with the linear relationship between the strain of the pipeline wall and the pressure inside the pipeline. The designed structure can enlarge and transmit the pipeline wall strain to the strain beam of the rhomboid structure. Next, simulation models for the pipeline, sensitization structure, and detection system were established. Afterward, a series of structural optimization tasks were performed. Simulation results of the analysis of the sensitization structure with different sizes show that the sensitization structure of the FBG sensor can amplify the strain of the pipeline wall several times. Besides, the test results indicate that the sensitized structure with a long diagonal of approximately 2.5 times the short diagonal and the rhomboid structure material of 7075 aluminum alloy has a more stable and effective transmission and amplification effect on the wall strain. Moreover, it can effectively amplify the measurement signal and has a high application value. Highlights: A rhomboid sensitization structure was proposed for nonintrusive pressure detection. The strain characteristics of the pipe wall under internal pressure were analyzed. Mathematical analysis and simulation of the sensitization structure were achieved. The sensitization structure is effective proven by fluid–solid coupling simulations. The good results have been gained from the pipeline pressure detection experiment.